The Presbyterian Church in the United States of North America - Ochoa Yumbla, Lorena
Presbyterianism in North America is a denomination that represents the features of Protestantism emphasized by John Calvin. Presbyterians mark out their history from the 16th century and the Protestant Reformation. The first representative assemblies took place during the early years of the next century. The church began to grow and develop its own indigenous leadership and educational, mission, and charitable institutions, as well as to experience its first internal conflicts. American Presbyterians not only faced growth over time, but their church split and later reunited several times. In spite of problems, Presbyterian participation in many important events has caused this denomination to have a considerable influence on United States history. This thesis contains the product of more than two years of survey. Following are short descriptions of the contents I have extracted in order to be used by readers as a guide